FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI - Wiegianto, Jessica Alvon; Surjadi, Lukman (Jurnal Paradigma Akuntansi, 2023)
This study aims to test and analyze whether there is influence between the structure of assets (tangibility), profitability, liquidity, and firm size on capital structure in manufacturing companies that have been listed in IDX during the period 2018-2020. This research, there are 80 companies to be studied by having the amount of data as much as 240 data. The company is using the secondary data in the form of financial statements of the company taken from the website IDX. The selection of the sample in this study using non probability purposive sampling method and the processing performed by using EViews 12. The results of the research that has been done shows that the structure of assets (tangibility) and profitability has no effect while the liquidity of the significant negative effect and firm size have a significant positive effect on capital structure.